P313 Reactivation of iconic memory in a priming task by transcranial magnetic stimulation (TMS). Issue 3 (March 2017) - Morand, S.; Gross, J.; Thut, G.
Abstract : Introduction: Iconic memory represents the registration of visual information in a high-capacity but fast decaying visuo-sensory buffer. It has recently been shown that the primary visual cortex contributes to this memory function. Objectives: In this TMS study, we investigated visual priming effects when TMS is applied over the primary visual cortex after prime presentation to see whether TMS could reactivate or "replay" the prime information stored in the sensory buffer. Methods: Prime and probe maintained the same shape (square) but varied in colours of the same mean luminance, leading to congruent vs incongruent prime-probe conditions. Observers (n = 14) were asked to identify the colour of the probe as accurately and as fast as possible. Each trial started by a fixation cross lasting between 500–2000 ms. A prime was then flashed for 10 ms within the lower RVF at the location of TMS-induced phosphenes. A probe was displayed 400 ms after the prime for 40 ms at a mirrored location in the lower LVF. In TMS blocks, single-pulse TMS below phosphene thresholds was randomly delivered at 100 ms or 300 ms after the prime onset and intermingled with no TMS trials. Control trials (with no TMS) aiming at emulating a possible TMS-induced replay consisted of a physical redisplay of the prime at 300 ms i) in the same but faint colour, ii) in the opponent colour or iii) of a grey mask while responses to probes were recorded. The design was the same in SHAM blocks. Results: Results showed that the significant priming effect (reaction times, RTs congruent  <  incongruent) observed in absence of stimulation was disrupted by TMS at 100 ms after the prime onset. Notably, this priming effect reverted to negative priming (RTs incongruent  <  congruent) for TMS at 300 ms. Comparison with the control trials attempting to emulate a physical re-appearance of the prime was suggestive of TMS at 300 ms inducing a recall of the prime in the colour opponent colour of the prime (no RT differences to opponent colour redisplays). Conclusion: This is evidence that a memory trace stored in the sensory buffer in V1/V2 can be reactivated by TMS. The study is supported by a Wellcome Trust Award to Gregor Thut and Joachim Gross [grant number 098434, 098433] and by a Biological Sciences Research Council (BB /I006494/1) grant.